Analisis Resepsi Pemain dalam Video Game “Among Us” - Ricky Widyananda Putra; Jeanie Annissa (PROPAGANDA, 2022)
Game is an entertainment facility that contains games using electronic devices which involve players who make decisions through control of game objects for certain purposes, known as users. The game growth industry has developed especially in a variety of types of games which include Maze Game, Board Game, Card Game, Battle Card Game, Quiz Game, Puzzle Game, Shooting Game, First Person Shooting (FPS), Side Scrolling Game, Fighting Game , Racing Game, Simulation, Strategy Game, Role Playing Game (RPG), Adventures Game, Sport Game, and Edutainment Game. In Indonesia itself, there are a variety of online games that have sprung up, among the many types of online games that are currently being talked about is the "Among Us" game. In the process of designing and developing the concept of a game, it is very important to get to know the user who is expected to be able to play the designed game. So that it can be seen the user's process in interpreting a game, this can be explored with various approaches, one of which is using reception analysis theory. Reception Study (study of acceptance) is one that develops in cultural studies, which focuses on messages or communication discourses and has implications for audiences. In this study, the game "Among Us" contained a narrative or storyline that was presented as well as a visualization of the character design of this game. The goal to be achieved in this research is to find out the meaning of players towards the Among Us game by using a Reception Study (acceptance study) which will focus on interpretive meanings and experiences of users or game users in interacting with game media.